Customer Satisfaction: A Game-Changer in Seller’s Adverse Selection - Kina, Nurul Fitri Rizkina; Yanthi, Merlyana Dwinda; Aini Haron, Nur Quratun (International Economic Conference of Business and Accounting, 2024)
Indonesia has potential for social commerce to grow, GMV was estimated US25 million last year. However, customers are experiencing passive and active opportunistic behavior among sellers which ultimately leads to higher seller uncertainty in social commerce than in e-commerce. Adverse selection occurs through pre-purchase uncertainty. Since satisfied customers are more likely to become loyal customers, customer satisfaction is an important performance indicator of a company’s effectiveness. Therefore, this study attempts to bridge this gap by investigating the influence of customer satisfaction on seller’s adverse selection. A self-administered structured questionnaire was used for data collection. The empirical evidence from 126 Tik Tok shop customers shows that the customer satisfaction indicators, positive review comments and seller’s services has a negative influence on seller’s adverse selection. Meanwhile, the seller’s popularity has not influence on seller’s adverse selection